GRANTING RESTITUTION AS A FORM OF LEGAL PROTECTION FOR CHILD VICTIMS OF SEXUAL VIOLENCE (ANALYSIS OF DECISION NO. 298/PID.SUS/2024/PN PLK) - Febi Riana Sinta; Tahasak Sahay; Rizki Setyobowo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Cases of sexual violence against children are a serious form of violation of human rights that cause deep suffering for victims both physically, psychologically, and socially. Restitution is an important instrument to restore victims' rights. This article aims to analyze the application of restitution as a form of legal protection for child victims of sexual violence based on Decision Number 298/Pid.Sus/2024/PN Plk. This study uses a normative juridical method with a qualitative approach. Data sources consist of court decisions as primary data and laws and legal literature as secondary data. The results of the study indicate that restitution in the decision has been implemented as a concrete form of legal protection for victims in accordance with the provisions of Article 7A of Law Number 31 of 2014 in conjunction with Law Number 13 of 2006 concerning Protection of Witnesses and Victims and Article 82 paragraph (1) of Law Number 17 of 2016 concerning Child Protection. The provision of restitution reflects a form of restorative justice that is oriented towards victim recovery rather than merely punishing the perpetrator. However, its implementation in the field still faces obstacles such as a lack of legal understanding and limited mechanisms for enforcing restitution decisions. This article emphasizes the importance of strengthening a legal system that is responsive to victims' needs by encouraging the implementation of restitution as a mandatory instrument in every child sexual violence decision.